ChemInform Abstract: Palladium‐Catalyzed Asymmetric Conjugate Addition of Arylboronic Acids to Heterocyclic Acceptors. Issue 20 (25th April 2013) - Holder, Jeffrey C.; Marziale, Alexander N.; Gatti, Michele; Mao, Bin; Stoltz, Brian M.
Abstract This method uses mild, aerobic conditions and an easily prepared catalyst system.